2021
DOI: 10.18805/ajdfr.dr-215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reproductive Performance of Jersey Cattle Raised under Semi-intensive Management in Ethiopia

Abstract: Background: The productivity and profitability of dairy cattle depend largely on reproductive performance. Thus, this study was intended to evaluate the reproductive performance of Jersey cattle raised under semi-intensive management system.Methods: A retrospective analysis consisted of data collected for the last 33 years was conducted. The fixed effects fitted were birth period, calving period, service period, birth season, calving season, service season, parity and genetic group. The general linear model pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…A relatively higher value for age at first calving was reported by Rehman et al (2008) in Sahiwal cows (1390 ± 3.9 days) and Moulick et al (1972) in Deshi cows (44.5 ± 6.8 months). Lower age of first calving was reported by Sherwin et al (2016), Jadhav et al (2019) and Beneberu et al (2021) for U.K. dairy herds (29.6 months), HF × Gir half breed cows (990.69 ± 6.53 days) and Jersey Cattle (32.95 ± 0.22 months), respectively. An Evaluation of the Reproductive Performance of Sahiwal Heifers in the High Humid Climatic Condition of Assam…”
Section: Age At First Calvingmentioning
confidence: 71%
“…A relatively higher value for age at first calving was reported by Rehman et al (2008) in Sahiwal cows (1390 ± 3.9 days) and Moulick et al (1972) in Deshi cows (44.5 ± 6.8 months). Lower age of first calving was reported by Sherwin et al (2016), Jadhav et al (2019) and Beneberu et al (2021) for U.K. dairy herds (29.6 months), HF × Gir half breed cows (990.69 ± 6.53 days) and Jersey Cattle (32.95 ± 0.22 months), respectively. An Evaluation of the Reproductive Performance of Sahiwal Heifers in the High Humid Climatic Condition of Assam…”
Section: Age At First Calvingmentioning
confidence: 71%
“…Similarly, the large variation of AFC attributed to the management level provided to individual cows at the farm level (Yadessa et al2021). In comparison, the overall least-square means for AFS and AFC for Jersey cattle raised under semi-intensive management in Ethiopia were 22.93 ± 0.22 months, and 32.95 ± 0.22 months (Beneberu et al 2021). Nonetheless, under smallholder conditions in and around Zeway, Ethiopia, the current AFC result is slightly higher than crossbred heifers in the urban (31.9 months) and rural (32.4 months) (Yifat et al 2009).…”
Section: Resultsmentioning
confidence: 89%
“…According to Duguma (2021), the reproductive performance of crossbred cows was better and lower due to delayed AFS, late AFC, long CI, shorter LL, low daily and LMY, and high NSC. On the other hand, management inconsistency and variability of climatic variables across year and season appear to have a signi cant in uence on cow reproductive e ciency (Beneberu et al, 2021). Hammoud et al (2010) demonstrated that the sire of the cow, management systems, and appropriate environmental conditions all have a signi cant in uence on the reproductive e ciency of Friesian cows in semiarid Egypt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations